Design and Construction of a Hydraulic Crane. - Twinamasiko, Nicholas (Kabale University, 2024)
This project aims to design and develop a hydraulic crane using locally sourced materials, exploring the principles of fluid pressure and mechanical advantage. The crane is constructed using six syringes, three connecting tubes, and various pieces of wood, nails, bicycle spokes, and rubber tubing. The system utilizes water as the hydraulic fluid wood glue and Cello tape for assembly. The crane's performance is tested by lifting loads of varying weights, demonstrating the application of scientific concepts in a real-world scenario. This project showcases the potential for innovative problem-solving and resourcefulness in engineering design, promoting sustainability and accessibility in technology development.